Making laws for clouds - Earls, Nick, 1963- (Camberwell, Vic. : Penguin Books, 2002)
It looks like this summer is going to be the best of Kane's life - he's got enough money for a meatosaurus pizza, and he's finally had a pash with Tanika Bell. Still, he's got a lot to figure out. Making Laws for Clouds is a collection of three novellas from the best selling Earls, one of which has already been published. Ages 15+.
The night sky from Battery Hill -- The stormy Deluxe -- Making laws for clouds.
Keywords: Young adult fiction; Humourous stories; Young adult fiction; Humourous stories. -- Young adult fiction